Extraskeletal chondroma of the fallopian tube. - Han, Jee-Young (Korean Academy of Medical Sciences, 2002)
Extraskeletal chondroma can occur in the hands, feet, head and neck. This tumor usually presents as a small solitary nodule. The histogenesis of the tumor is controversial, but some have suggested a metaplastic origin. Chondroma of the fallopian tube is very rare. There is only one report in English literature. The origin of this tumor can be subcoelomic mesenchyme of the tubal serosa or mesenchyme of the myosalpinx. We describe a case of chondroma arising from the serosal surface of the fallopian tube with a review of literature. A 30-yr-old woman visited hospital due to left adnexal mass. On operating finding, 2 x 3 cm sized nodular mass was noted on the left tubal serosal area. The excised mass showed multilobulated appearance covered with thin fibrous membrane. The cut surface was solid, grayish yellow, and myxoid with a focal gelatinous area. The microscopic finding showed islands and elongated lobules of mature benign cartilage without cytologic atypia.